THE COMPARISON OF STRATEGIES USED IN TRANSLATING IDIOMATIC EXPRESSIONS IN A FANSUB AND THE OFFICIAL SUBTITLE OF GAME NIGHT MOVIE (2018) - Putri, Fatmasari; Wijaya, Andika (UI Scholars Hub, 2021)
Characters in a movie often use idioms in various situations to express certain ideas. However, translating idioms can be challenging for translators making the movie subtitle. This descriptive-qualitative research aims to examine the types of idioms that appear in Game Night movie (2018) and compare the strategies used in the fansub and the official subtitle of the movie in translating idiomatic expressions. The data analyzed in this research consist of all the idioms that appear in the movie and their Indonesian translations. The results of this study show that English phrasal compounds constitute the most frequently used type of idiom. Meanwhile, the most used translation strategy in both the fansub and the official subtitle is the translation by paraphrase strategy. Despite the application of the same strategy, there are still some differences in the translations of the same idioms between the two subtitles. Meanwhile, other translation strategies are used in different frequencies. Overall, the study finds the official subtitle to be more communicative than the fansub translation.